Inventor’s Legal Liability upon the Invention of Artificial Intelligence in Indonesia - Deslaely Putranti; Kurnia Dewi Anggraeny (Varia Justicia, 2022)
The pace of technological development can no longer be restrained until the emergence of artificial intelligence (AI), which later turns out to negatively impact its application. AI is a computer system program created by humans. On the one hand, the invention of AI makes human work easier. On the other hand, it is also noticeable that there are several criminal cases "performed" by AI. This research is qualitative research with doctrinal approach. The data used include secondary data consisting of primary, secondary, and tertiary legal materials. The method of data collection is done through document study. The research concludes that the inventor of an invention of artificial intelligence can be charged with legal responsibility by applying the limits of liability both in civil and penal sanction. Further studies are needed to answer the question of how far this responsibility can be carried out.